Green areas and the social and environmental impact in the city of Ribeirão Preto - Toni Jr, Claudio Noel de [UNESP] (Pontificia Univ Catolica Sao Paulo-puc-sp, 2024)
This research aims to evaluate the importance of green areas in promoting happiness and well-being in the population of the city of Ribeir & atilde;o Preto, SP, with an emphasis on studies on urban afforestation. The referential bibliographic material used will be based on the Urban Project Protocol (2010), as well as by authors like Paul Dolan, who explains human happiness. The use of geotechnologies is essential for the mapping of the area, aiming at the analysis of afforestation and the selection of suitable species of these in public spaces, the greater the selection of sustainable trees for this purpose, which is the capture of emission gases greenhouse effect (GHG), so one must monitor tree species for this purpose. In times of pandemic, where people are restricted to walks, look at themselves, have feelings of satisfaction and purpose in their lives, perceive and believe in this new normal, which will be built over the years, the experience of contact with people with green areas, it can bring purpose to change the perception of their lives, to glimpse new horizons and possibilities of being happy. The work contemplates aspects of happiness related to green areas. How to be happy, have pleasure and well-being, in the pandemic and in the post-pandemic? With the Urban Project Protocol Report approach, as well as the selection of sustainable trees, one can contribute to urban planning and local public policies.
Keywords: Urban Afforestation; Human Happiness; Pandemic; Geotechnologies